The Oxford companion to American literature - Hart, James D. (James David), 1911-1990.; Leininger, Phillip, 1928-; Oxford University Press ([ New York] : Oxford University Press, 1995)
Online version of the print ed. which lists ofer 2,000 biographical profiles of important American authors (with information regarding their style, subjects, and major works) and influential foreign writers as well as other figures who have been important in the nation's social and cultural history. There are more than 1,100 full summaries of important American novels, stories, essays, poems (with verse form noted), plays, biographies and autobiographies, tracts, narratives, and histories.
"Oxford reference online. Premium."
Title from home page (viewed on Feb. 5, 2004).
Also issued in print format.
Mode of access: World Wide Web.
Keywords: American literature -- Bio-bibliography.; American literature -- Bio-bibliography.; American literature -- Dictionaries; Authors, American -- Biography -- Dictionaries